BPJS Health Bureaucracy in Providing Public Services - Ramadha Yanti Pariduri; Barham Siregar; Cut Sah Kha Mei Zsazsa (International Journal on Social Science, Economics and Art, 2024)
This research discusses how the BPJS Health bureaucracy provides public services. BPJS Health which includes aspects of clarity, security, openness, fairness and timeliness. Can explain public services well. This research uses a qualitative approach. The data analysis techniques used are data reduction, data display (data presentation) and conclusion drawing/verification (summarizing). This research shows that since the implementation of the BPJS policy, people's interest in having a health card has increased significantly, especially among the lower middle class who previously had difficulty accessing health services. This shows that the BPJS policy has succeeded in increasing the accessibility and availability of health services for the Indonesian people. Bureaucracy or procedures in public services at BPJS offices using a qualitative method approach, the results of which show that bureaucracy or public service procedures at BPJS offices are generally in accordance with established regulations and are easily accessible.